Dietary patterns of adults and their associations with Sami ethnicity, sociodemographic factors, and lifestyle factors in a rural multiethnic population of northern Norway - the SAMINOR 2 clinical survey - Petrenya, Natalia; Rylander, Charlotta; Brustad, Magritt (BMC Public Health, 2019)
Background - Few population-based studies have assessed dietary behaviors in the rural multiethnic population of Northern Norway. The present study determined dietary patterns and investigated their association with Sami ethnicity, sociodemographic factors, and lifestyle factors in a multiethnic population in rural Northern Norway. Methods - This cross-sectional study included 4504 participants of the SAMINOR 2 Clinical Survey (2012–2014) aged 40–69 years. All participants completed a lifestyle and food frequency questionnaire. Dietary patterns were determined using principal component analysis. Associations between food patterns and ethnicity, sociodemographic factors, and lifestyle factors were examined by multiple linear regression. Results - Six dietary patterns were identified that accounted for 28% of the variability in food intake in the study sample: ‘processed meat/westernized’, ‘fish/traditional’, ‘fruit/vegetables’, ‘reindeer/traditional’, ‘bread and sandwich spreads’, and ‘sweets and bakery goods’. The ‘reindeer/traditional’ pattern was most common among the inland Sami population. The ‘fish/traditional’ pattern was most common among costal multiethnic Sami and least common among inland Sami and among women independent of ethnicity. The ‘fish/traditional’ pattern was also positively associated with older age, high education level, small household size, and smoking. Adherence to the ‘processed meat/westernized’ pattern was lower among inland Sami than inland/coastal non-Sami; no ethnic differences in adherence to this pattern were found between costal multiethnic Sami and inland/coastal non-Sami. Unhealthy lifestyle factors, like low physical activity level and smoking, and younger age were mainly associated with the ‘processed meat/westernized’ pattern, whereas socioeconomic factors like low education, low gross annual household income, and large household size were related to the ‘sweets and bakery goods’ pattern. Male gender, low education level, and smoking were associated with the ‘bread and ...